The role of cytology and other prognostic factors in endometrial cancer. (October 2013) - Kyrgiou, M.; Chatterjee, J.; Lyus, R.; Amin, T.; Ghaem-Maghami, S.
<x xml:space="preserve">Abstract</x> The clinical and prognostic value of positive cytology in women with endometrial cancer remains uncertain. The aim of our retrospective observational study was to determine whether in women with disease confined to the uterus, positive peritoneal cytology adversely affects disease-free (DFS) or overall survival (OS); to assess whether positive or negative cytology affects survival in women irrespective of stage and to assess whether the use of hysteroscopy or Pipelle for diagnosis affected cytology positivity rates. We have shown that median DFS and OS were almost identical for tumours confined to the uterus with and without positive peritoneal cytology. Women with tumours extending to the serosa or adnexa had a non-statistically significant shorter survival in comparison with women with stage I disease and negative cytology. Out of 59 women that had their cancer diagnosis based on a Pipelle biopsy of the endometrium, five had positive peritoneal washings. A total of 150 women had pre-treatment hysteroscopy; seven of these had positive peritoneal washings. There was no significant difference in the rates of positive cytology between these groups (4.6% vs 8.4%). In our cohort of un-staged women, positive peritoneal cytology did not adversely affect prognosis when disease was confined to the uterus.